PHYSIOPATHOLOGICAL MECHANISMS IN THE RELATIONSHIP BETWEEN SMOKING AND PERIODONTAL DISEASE - Amelia Surdu; Irina-Georgeta Sufaru; Ioana Martu; Ovidiu Sebastian Nicolaiciuc; Monica Mihaela Scutariu (Romanian Dental Association for Education, 2019)
ABSTRACT The systemic and oral effects caused by the use of passive or active tobacco in general and oral health are considerably high throughout the world. The negative effects of smoking habits on health depend on the dose and type of compounds of cigarettes, as well as the frequency and timing of exposure. Smoking is the main modifiable risk factor for periodontitis. Clinical studies are unanimous in demonstrating that smokers have increased susceptibility to periodontitis and greater severity and progression of periodontal disease compared to non-smokers. Paradoxically, the signs and symptoms of gingival inflammation are less pronounced in smokers than in non-smokers.